2018
DOI: 10.1021/acsanm.8b00567
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Ruthenium Decorated Zr0.5Ce0.5O2 Nanorods for Catalytic Partial Oxidation of Methane

Abstract: Nanosized Ru (1 wt %) supported over CeO 2 − ZrO 2 solid solution nanorods have been prepared via a one step hydrothermal approach and verified its activity in partial oxidation of methane at 800 °C with CH 4 : O 2 = 2:1 for 200 h in a downflow, fixed-bed, microreactor. The so prepared catalysts have been characterized with a variety of analytical tools. Characterization results confirm higher dispersion of nanosized Ru over CeO 2 −ZrO 2 solid solution possess strong metal support interaction and higher oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…The high surface areas offered by small particles of ceria-zirconia prepared by solvothermal routes are suited to act as supports for precious metal nanoparticles in heterogeneous catalysis, and, indeed, some of the examples reported in Table 1 were used for this purpose, with the precious metals added in a subsequent step [46]. Taking a different approach, Das et al used a one-step approach to prepare such catalysts, by inclusion of ruthenium chloride in the hydrothermal reaction of cerium and zirconium chlorides, with hydrazine present as a reducing agent and CTAB as a structure-influencing agent [50]. After a mild calcination, the material consisted of Ce 0.5 Zr 0.5 O 2 nanorods with a fine dispersal of Ru nanoparticles; these proved effective catalysts for the partial oxidation of methane.…”
Section: Ceria-zirconiamentioning
confidence: 99%
“…The high surface areas offered by small particles of ceria-zirconia prepared by solvothermal routes are suited to act as supports for precious metal nanoparticles in heterogeneous catalysis, and, indeed, some of the examples reported in Table 1 were used for this purpose, with the precious metals added in a subsequent step [46]. Taking a different approach, Das et al used a one-step approach to prepare such catalysts, by inclusion of ruthenium chloride in the hydrothermal reaction of cerium and zirconium chlorides, with hydrazine present as a reducing agent and CTAB as a structure-influencing agent [50]. After a mild calcination, the material consisted of Ce 0.5 Zr 0.5 O 2 nanorods with a fine dispersal of Ru nanoparticles; these proved effective catalysts for the partial oxidation of methane.…”
Section: Ceria-zirconiamentioning
confidence: 99%
“…According to Li et al, the introduction of Zr 4+ in the CeO 2 lattice also promotes the activation of CO 2, resulting in improved catalytic activity. Our previous work with Ru supported ceria-zirconia mixed composites confirmed their higher OSC with enhanced stability toward methane reforming reaction …”
Section: Introductionmentioning
confidence: 67%
“…Generally, the supports’ conductivity has been identified as a favorable property compared to insulating supports like alumina due to better migration of adsorbed oxygen that prevents coke accumulation and subsequent deactivation. , Ceria is well-known for its excellent oxygen storage capacity (OSC). ,, However, OSC degradation at high temperatures has been found in an extended activity study with ceria-based catalysts . Moreover, previous findings have established that ZrO 2 is a unique support for several catalytic reactions due to its high thermal stability. , Therefore, doping of ceria with zirconia is believed to enhance the specific surface area’s stability by suppressing thermal sintering. , However, it has been observed that ceria-zirconia mixed oxides with low surface area still maintain a high OSC compared with undoped ceria. ,, Over ceria, the Frenkel-type defects disappeared at high temperatures due to the recombination of octahedral interstitial ions with the tetrahedral oxygen vacancies. In contrast, the 23Wpresence of the smaller zirconium ions causes compressive stresses at the spatially tight tetrahedral sites, resulting in enhanced OSC in mixed ceria-zirconia systems .…”
Section: Introductionmentioning
confidence: 99%
“…Even after testing at 750°C for 140 h, the catalyst maintained a CH 4 conversion of 86% and CO selectivity of 94%. Besides, Ru nanoparticles supported over Ce 0.5 Zr 0.5 O 2 nanorods obtained by Das et al 120 were proven to be more active than Ru/CeO 2 and Ru/ZrO 2 . Specifically, the stronger metal-support interactions and higher oxygen storage capacity of the CeO 2 -ZrO 2 solid solution contributed to the increased catalytic performance.…”
Section: Methane Oxidation Reactionmentioning
confidence: 93%